1996
DOI: 10.1139/b96-225
|View full text |Cite
|
Sign up to set email alerts
|

Successive pot cultures reveal high species richness of arbuscular endomycorrhizal fungi in arid ecosystems

Abstract: Three cycles of successive trap cultures were utilized to determine the taxonomic structure of arbuscular fungi associated with mesquite (Prosopis spp.) from three locations in the Sonoran desertscrub biotic community and one location in the Chihuahuan desertscrub biotic community. Unlike the low species richness found in previous studies of some arid habitats, seven to nine species were recovered from each sampling site. This number is comparable to that found in many other plant communities. Seventy-five per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
2
14

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(135 citation statements)
references
References 29 publications
9
110
2
14
Order By: Relevance
“…As suggested by Stutz and Morton (1996), the low levels of sporulation reported in other desert soil surveys (Rose, 1981;Pond et al, 1984;Cui and Nobel, 1992), as well as their own detection of many non-sporulating VAM fungal species, indicate that lack of sporulation is a common if not predominant phenomenon in some arid regions. This makes it initially difficult to evaluate species diversity in any particular study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As suggested by Stutz and Morton (1996), the low levels of sporulation reported in other desert soil surveys (Rose, 1981;Pond et al, 1984;Cui and Nobel, 1992), as well as their own detection of many non-sporulating VAM fungal species, indicate that lack of sporulation is a common if not predominant phenomenon in some arid regions. This makes it initially difficult to evaluate species diversity in any particular study.…”
Section: Discussionmentioning
confidence: 89%
“…was found in two samples, only in the UC soils. The difficulty in increasing spore populations from native soils with low or non-sporulating endophyte populations is not uncommon, and may require multiple, successive trap-culture cycles to detect species diversity (Stutz and Morton, 1996).…”
Section: Isolation Of Vam Fungal Endophytesmentioning
confidence: 99%
“…Esta espécie não produziu esporos no experimento 1, como também não foram detectados esporos no material original. No entanto, sabe-se que cultivos sucessivos ou mais prolongados favorecem a esporulação de número maior de espécies, especialmente as mais raras (Stutz & Morton 1996). Há vários relatos de ocolTência de A. appendicula em ecossistemas brasileiros (Fernandes & Siqueira 1989;Siqueira et aI.…”
Section: Resultsunclassified
“…Conversely, results of van der Heijden et al (1998) on the relation between AMF and plant diversity were not observed in this study. However, we recognize that our measurement of AMF diversity probably does not represent the entire fungal community as it does not account for cryptic non-sporulating species colonizing plant roots (Stutz & Morton 1996).…”
Section: Number Of Viable Sporesmentioning
confidence: 99%